2022
DOI: 10.1111/jam.15643
|View full text |Cite
|
Sign up to set email alerts
|

Exploring of probiotic potential vaginal lactobacillus isolates from healthy women against Gardnerella vaginalis and Caenorhabditis elegans model testing

Abstract: Aim: Lactobacillus species are the dominant microorganisms in the vaginal microbiota of healthy women and play an important role in the defence against pathogens.This study aimed to evaluate probiotic potential of Lactiplantibacillus plantarum strain P1 isolated from healthy woman's vaginal discharge for its further utilization as a promising candidate strain in the treatment of bacterial vaginosis caused by Gardnerella vaginalis.Methods and Results: Ten lactobacilli strains from a woman's vaginal discharge we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…In the absence of this barrier, during a period of active cell replication such as that occurring in the presence of immature metaplasia or cervical ectropion, in a state of cellular inflammation, and in the presence of contributing factors such as altered vaginal pH, various pathogens can replicate more easily and disrupt the normal resident microbiota [ 11 , 12 ]. Our results align with previous research highlighting the importance of a balanced vulvo-vaginal environment in maintaining vaginal health [ 10 , 13 , 14 , 15 , 16 , 17 ]. These findings are consistent with the emerging understanding that preserving a stable vaginal microbiome may be more beneficial than the use of antibiotics or antiviral agents alone in managing various cervico-vaginal infections.…”
Section: Discussionsupporting
confidence: 92%
“…In the absence of this barrier, during a period of active cell replication such as that occurring in the presence of immature metaplasia or cervical ectropion, in a state of cellular inflammation, and in the presence of contributing factors such as altered vaginal pH, various pathogens can replicate more easily and disrupt the normal resident microbiota [ 11 , 12 ]. Our results align with previous research highlighting the importance of a balanced vulvo-vaginal environment in maintaining vaginal health [ 10 , 13 , 14 , 15 , 16 , 17 ]. These findings are consistent with the emerging understanding that preserving a stable vaginal microbiome may be more beneficial than the use of antibiotics or antiviral agents alone in managing various cervico-vaginal infections.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, in mouse vaginal tissue lysates, a combination of five lactobacilli strains can greatly inhibit G. vaginalis proliferation and considerably lower myeloperoxidase activity, pro-inflammatory cytokine levels (TNF-α, IL-1β, and IL-6), and nitric oxide levels ( Choi et al., 2022 ). In experiments using a Caenorhabditis elegans model, L. plantarum strain P1 has shown potent antibacterial action against G. vaginalis and considerably prolonged the lifespan of C. elegans after exposure to infection agents ( Li et al., 2022 ).…”
Section: Probiotic Lactobacilli In the Treatment Of Vaginal Infectionsmentioning
confidence: 99%
“…Perhaps because VMT is introduced into the vagina as a whole system, allowing the microbiota to maintain better stability, and VMT contains bacteria that are not present in the synthetic preparation. However, the bacterial strains we selected for SBCT were able to produce natural antibacterial products such as hydrogen peroxide and lactic acid to resist pathogenic bacteria [ 30 ]. Previous studies reported that oral or vaginal administration of a Lactobacilli mixture could attenuate GV-inoculated mice by regulating the innate and adaptive immune responses [ 20 ].…”
Section: Discussionmentioning
confidence: 99%